Macroeconomic determinants of housing prices in Iceland : an empirical analysis for the period from 2001 to 2021 - Nikólína Dís Kristjánsdóttir 1998-; Sigurður Örn Alfonsson 1998- (2022)
Investing in a house could be considered as one of the most important decisions of your life. As the housing market has been a popular topic lately, due to the enormous increase in housing prices, it is important to recognize the factors that affect housing prices in order to avoid housing booms and busts. However, housing prices can be affected by various factors, as well as the factors that have the most impact vary between countries. Therefore, this thesis attempts to recognize the macroeconomic factors that have affected housing prices in Iceland for the last 20 years, more precisely from the year 2001 to 2021. The results from the research suggest that building costs have the largest positive effect on housing prices while the private sector housing stock has the largest negative effect on housing prices. Other significant factors that influence housing prices in Iceland include gross domestic production per capita, equity prices, population at working age, and the consumer confidence index.